2009
DOI: 10.1163/156921009x413144
|View full text |Cite
|
Sign up to set email alerts
|

Do Physical and Human Capital Matter for Export Diversification?: A Comparative Analysis of Sub-Saharan Africa and East Asia

Abstract: This paper examines the effects of physical and human capital on vertical and horizontal export diversification using a 30-year panel data of 41 countries from Sub-Saharan Africa (SSA) and East Asia for the years 1975-2004, while accounting for othtr factors. Accordingly, the empirical results revealed rhar human capital and domestic investment are indeed the key factors to induce venlcal and horizontal export diversification though the magnitudes of their coefficients arc highest in East Asia and less in SSA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Vertical export diversification is generated in the economy through positive externalities “learning by doing” and refers to the increase in the value of existing commodity through innovation and creativity. Mengistu (2009) argued that vertical export diversification is an essential component of economic growth. The results of the model with horizontal and vertical export diversification are presented in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…Vertical export diversification is generated in the economy through positive externalities “learning by doing” and refers to the increase in the value of existing commodity through innovation and creativity. Mengistu (2009) argued that vertical export diversification is an essential component of economic growth. The results of the model with horizontal and vertical export diversification are presented in Table II.…”
Section: Resultsmentioning
confidence: 99%
“…While Lee et al (2018) observed that human capital complementarities motivated Income diversification in East African banks mergers and acquisitions and led to improved post-merger financial performance. Similarly, Mengistu (2009) found that human capital influenced vertical and horizontal export diversification. By and large, these studies emphasize that knowledge-based resources can be leveraged through diversification for economic rent.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Another branch of variables considers a country's education system. Various studies propose schooling to play a substantial role in export diversification, e.g., Mengistu (), Parteka and Tamberi (), or Agosin, Alvarez, and Bravo‐Ortega (). To this end, we include five education variables: the duration of primary and secondary education, secondary and tertiary enrollment rates (gross percentage), and total primary enrollment (net percentage) .…”
Section: Variablesmentioning
confidence: 99%